Research priorities for irrigation management in Asia: An overview of research in irrigation management in Asia - Small, L.E.; Barker, Randolph (International Irrigation Management Institute, 1985)
Presents two papers that provide interpretive summaries of the discussion and results of the Workshop on the Research Priorities for Irrigation Management in Asia held from 6-11 January 1985 at the headquarters of the International Irrigation Management Institute (IIMI) in Digana Village near Kandy, Sri Lanka. Dr. Small's paper, "Research priorities for irrigation management in Asia," provides a conceptual framework for irrigation management research and outlines criteria for IIMI's selection of research topics. "An overview of research in irrigation management in Asia" by Dr. Barker summarizes the conceptual evolution of irrigation management in terms of both conventional disciplinary and holistic, systems-oriented approaches.